Creation of Promotional Media for MineRO Water Business “Yatimmu” - Rusnandari Retno Cahyani; Anniez Rachmawati Muslifah (Indonesian Journal of Society Development, 2023)
This service activity is carried out by a business unit that is being pioneered by the Muhammadiyah Orphanage Setrorejo Baturetno Wonogiri Regency. Aiming to provide a form of assistance in the form of: (1) making business promotion media (2) participating in promotional activities, (3) making a circulation of pricelist prices and benefits from MinerRO. The business problem faced is that it is ready to start but has not yet done a promotion to be known to the public and the surrounding community, besides that the promotion that will be carried out by the team does not yet exist. The results of this activity help and facilitate promotion in the early stages of a business startup. So it is hoped that a lot of help from academies, non-profit institutions and local governments and the community to participate in providing convenience and helping the process of running a startup business so that it can develop by carrying out further activities and at the same time sustainability